Mapping Of Private Higher Education Strategies In Formulating Strengthening Competitiveness With Swot Analysis Approach (Strents, Weakness, Opportunities, Threats) - Kafrawi, Kafrawi; Fahrina Yustiasari Liriwati; M. Ilyas; Abdul Syahid; Mulyadi, Mulyadi (Cita konsultindo, 2022)
The competitiveness of private tertiary institutions is interpreted as the provision of higher education services for the community (public) that are of superior quality, competitive and able to satisfy all stakeholders.The competitiveness of Higher Education is sexy and interesting to be studied, because this unit plays an important role in producing professional Human Resources to enter the world of work. At the same time, universities must be successful in implementing the tridharma of Private Higher Education in the form of teaching, research, and community service. So that the community really enjoys the existence of these tertiary institutions to raise the standard of living of the community. The competitiveness of private tertiary institutions provides a moral message that strength creates excellence, or there is a difference based on production quality, the tridharma services of tertiary institutions must be the best. The meaning of power must be interpreted by State Universities and Private Universities in order to make the resources owned superior to other Universities in certain aspects. SWOT analysis (Strength, Weakness, Opportunity, Threats) is a process of identifying or in-depth study of various factors systematically to formulate various organizational strategies, for example universities in maximizing strengths and opportunities, as well as minimizing weaknesses and threats (threats) that may occur and be faced by the various work units within it in order to evaluate the various output products produced and the tridharma services provided as well as by competitors of similar tertiary institutions.